Geographies of girlhood : identities in-between - Bettis, Pamela, 1955-; Adams, Natalie G. (Inquiry and pedagogy across diverse contexts., 2005)
Explores how diverse adolescent girls come to understand themselves as female in this culture, particularly during a time when they are learning what it means to be a woman and their identities are in between those of child and adult, girl and woman.